2020
DOI: 10.1002/chem.201905745
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry‐Controlled Supramolecular Architectures of New Tetrahydroxy‐Functionalised Amphiphilic Carbocyanine Dyes

Abstract: The syntheses of novel amphiphilic5 ,5',6,6'-tetrachlorobenzimidacarbocyanine( TBC) dye derivatives with aminopropanediol head groups, whicho nly differ in stereochemistry (chiral enantiomers, meso form and conformer), are reported. For the achiral meso form, an ew synthetic route towards asymmetric cyanine dyes was established. All compounds form Ja ggregates in water,t he opticalp roperties of which were characterised by means of spectroscopic methods. The supramolecular structure of the aggregates is invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…These hydrophilic groups include mainly sulfonic acid group, quaternary ammonium cation, and PEG blocks. The aggregation of amphiphilic dyes in water is driven by multiple different forces, mainly including hydrophilic and hydrophobic interactions, π-π interactions between planes of chromophores as well as steric hindrance of substituent groups (Schade et al, 2020). Early in the last century, the J-aggregation of ICG and other amphiphilic cyanine dyes in aqueous solution was discovered (Mishra et al, 2000).…”
Section: Hydrophilic/hydrophobic Interactionsmentioning
confidence: 99%
“…These hydrophilic groups include mainly sulfonic acid group, quaternary ammonium cation, and PEG blocks. The aggregation of amphiphilic dyes in water is driven by multiple different forces, mainly including hydrophilic and hydrophobic interactions, π-π interactions between planes of chromophores as well as steric hindrance of substituent groups (Schade et al, 2020). Early in the last century, the J-aggregation of ICG and other amphiphilic cyanine dyes in aqueous solution was discovered (Mishra et al, 2000).…”
Section: Hydrophilic/hydrophobic Interactionsmentioning
confidence: 99%
“…39 LHNs also possess a strong circular dichroism signature, though the structural origin of this chirality is yet to be elucidated. 38,[40][41][42][43] Extended Data Table 1 shows a literature survey of structural studies on pristine LHNs, their methodologies and key findings. As shown in Extended Data Table 1, all the nanoscale structural information was derived from low-resolution electron microscopy, excitonic modeling, and molecular dynamics simulations that were validated by comparing to the optical spectra.…”
Section: Light Harvesting Nanotubes (Lhns)mentioning
confidence: 99%
“…Recent atomistic simulations of the C8S3 bilayer concluded that the octyl tails should be splayed and strongly interdigitated, to balance the area deficit . However, the estimated bilayer thickness on the order of ∼2.5 nm proved to be too small compared with the experimental cryogenic transmission electron microscopy (cryo-TEM) data, amounting to about 4 nm. ,, A second characteristic of C8O3 and C8S3 tubes pointing to unbalanced molecular packing is known for a long time but is so far unexplained: the isolated tubes are not stable but tend to form hexagonally packed bundles after longer storage in solution, , in particular when alcohols are present. , By using cryogenic electron tomography (cryo-ET), , it has been shown that the outer chromophore layer of individual tubes is lost during the bundling process, finally leading to a hexagonally packed assembly of single-layered tubes with a water-filled interior. This morphology can be considered as the precursor of an inverse hexagonal liquid-crystalline phase (H II ), typical of lipids .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the aggregation behavior of a class of derivatives of the well-known 5,5′,6,6′-tetrachlorobenzimidacarbocyanine (TBC) chromophore has been investigated by several groups using a wide range of analysis and characterization methods. The dye was diversely functionalized by attaching different polar or non-polar substituents at the nitrogen atoms in the 1,1′- and 3,3′-positions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation